PELATIHAN PEMBUATAN PRODUK ABON JAMBU MENTE DI DESA SEKOTONG TENGAH - Maulidin, Maulidin; Rachman, Irna Ningsi Amalia; Irawan, M. Ary; Suminar, Tiassari Janjang; Wardani, Intan Kusuma (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The utilization of cashew fruit flesh in Sekotong Tengah Village is still very limited and is often considered waste, even though it has superior nutritional content with vitamin C levels five times higher than oranges. Seeing this potential, a cashew floss product production training program was initiated with the main objective of optimizing neglected local resources and turning them into products of high economic value. This activity specifically targets PKK mothers and local youth as agents of change to improve productive skills at the community level. The implementation method is designed comprehensively, starting with a counseling session on nutritional potential and business opportunities, followed by a demonstration and direct practice of making floss step by step. The results showed a significant increase in participants' knowledge and skills in processing cashew nuts. In addition, innovation in product packaging equipped with modern labels has proven to be successful in drastically increasing the appeal and selling value. Ultimately, this activity not only has a positive impact on the local economy by creating new business opportunities, but also becomes a model for developing sustainable natural resource-based products. ABSTRAKPemanfaatan daging buah jambu mete di Desa Sekotong Tengah masih sangat terbatas dan seringkali dianggap sebagai limbah, padahal memiliki kandungan nutrisi superior dengan kadar vitamin C lima kali lebih tinggi dari jeruk. Melihat potensi ini, program pelatihan pembuatan produk abon jambu mete diinisiasi dengan tujuan utama untuk mengoptimalkan sumber daya lokal yang terabaikan dan mengubahnya menjadi produk bernilai ekonomi tinggi. Kegiatan ini secara khusus menyasar ibu-ibu PKK dan para pemuda setempat sebagai agen perubahan untuk meningkatkan keterampilan produktif di tingkat komunitas. Metode pelaksanaan dirancang secara komprehensif, diawali dengan sesi penyuluhan mengenai potensi gizi dan peluang usaha, dilanjutkan dengan demonstrasi dan praktik langsung pembuatan abon tahap demi tahap. Hasilnya menunjukkan peningkatan signifikan pada pengetahuan dan keterampilan peserta dalam mengolah jambu mete. Selain itu, inovasi pada pengemasan produk yang dilengkapi label modern terbukti berhasil meningkatkan daya tarik dan nilai jual secara drastis. Pada akhirnya, kegiatan ini tidak hanya memberikan dampak positif bagi perekonomian lokal dengan menciptakan peluang usaha baru, tetapi juga menjadi model pengembangan produk berbasis sumber daya alam secara berkelanjutan.